Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Solve for n in the literal equation a(n − 5) + 6 = bn.

Sagot :

Answer:

(6-5a)/(b-a) = n

Step-by-step explanation:

a(n − 5) + 6 = bn

Distribute

an -5a +6 = bn

Subtract an from each side

an -5a+6 -an = bn-an

6-5a = bn-an

Factor out n

6-5a = n(b-a)

Divide each side by (b-a)

(6-5a)/(b-a) = n

Answer:

[tex]a(n - 5) + 6 = bn \\ an - 5a + 6 = bn \\ an - bn = 5a - 6 \\ n(a - b) = 5a - 6 \\ n = \frac{5a - 6}{a - b} \\ thank \: you[/tex]